Kebijakan Pemerintah Dalam Mewujudkan Strategi Coastal Defense dengan pendekatan Anti-Access Area Denial (A2/AD) Sebagai Pertahanan Di Kawasan Indonesia - Prastyo, Yudo (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This study examines Indonesia’s coastal defense policy using an Anti-Access/Area Denial (A2/AD) strategy to protect its coastal regions. The A2/AD approach is adapted to the geographical characteristics of Indonesia as an archipelagic state, involving maritime radar surveillance, strengthening coastal patrol fleets, and developing access denial tactics in strategic areas like the Malacca Strait and the North Natuna Sea. Key threats, such as foreign vessel infiltration and illegal activities, drive the adoption of this strategy. A qualitative method is employed, analyzing policy documents, including the Indonesian Navy’s Strategic Plan, interviews with relevant officials, and case studies of the Nusantara Maritime Surveillance System (SPILN). The analysis reveals progress in infrastructure development, such as coastal base construction and defense equipment modernization. However, challenges remain, particularly in inter-agency coordination involving the Navy, Maritime Security Agency (Bakamla), and the Ministry of Marine Affairs and Fisheries, as well as limited resource allocation. The Fast Patrol Boat program exemplifies these issues, with operational constraints due to inadequate integration with national surveillance systems. Recommendations include enhancing policy synergy through a unified command center, optimizing maritime defense budgets, and improving tactical training for coastal units. These findings aim to guide policymakers in formulating a more effective coastal defense strategy to safeguard Indonesia’s maritime sovereignty and security.